Kombinasi Cipher Subtitusi (Beaufort Dan Vigenere) Menggunakan Pembangkit Kunci RC4 Pada Kriptogtrafi Video Audio Video Interlaced (AVI) - Boru, Meiton; Sultani, Akhzan Akbar; Mauko, Arfan Yehezkial; Mola, Sebastianus Adi Santoso; Letelay, Kornelis; Sihotang, Dony Martinus (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2024)
Cryptography is the science of information security which is the most fundamental basic issue in ensuring the security of data transmission via the web. Cryptography works by transforming data or information into random form. Video data is the most widely accessed information medium because video conveys information in audio and visual form. In this study, cryptography was carried out on AVI video files with a combination of Beaufort and Vigenere substitution cipher algorithms using the RC4 key generator. Testing was carried out on three groups of video sample test data based on the size of the video file, where each group contained 10 video files. The test results obtained an average time required for encryption of 17 minutes 17 seconds, decryption of 17 minutes 40 seconds. The quality is indicated by the algorithm, namely from data integrity with an MSE value of 0 and a PSNR value of infinte, from the resulting cipher having an average value of MSE ± 15883 and PSNR ± 0.612 dB on audio, and an average value of MSE ± 14173 and PSNR ± 0.674 dB on frames. Resolution and video file size as well as initial key length do not significantly affect MSE and PSNR values. Statistically, the frequency range of color appearance in the histogram of cipher frames becomes narrower and relatively uniform. Waves in the audio cipher against time units move irregularly with changing sound level amplitudes and are relatively uniform in each audio sample. The resistance of the cipher to attacks is proven by the audio in three groups giving an average MSE of ± 16074 and PSNR of ± 0.607 dB, while for frames in three groups giving an average MSE of ± 15941 and PSNR of ± 0.623 dB.